ON THE QUESTION OF THE CONCEPT AS A REFLECTION OF THE LANGUAGE PICTURE OF THE WORLD (Academicia Globe: Inderscience Research, 2022)
This article discusses the national linguistic picture of the world, which is expressed in the mentality of the nation, reflecting the basic concepts and notions.